Touristic destination image in light of the service dominant logic of marketing - Edar da Silva Añaña; Francisco Antonio dos Anjos; Melise de Lima Pereira (Tourism & Management Studies)
This paper analyzes the composition and internal arrangement of touristic seaside destinations in Brazil, in light of three not-yet tested theories: the Means-End Chain (Gutman, 1982), the Service Dominant Logic of Marketing (Vargo & Lusch, 2004), and the organizational triad for local development proposed by Vázquez-Barquero (1999). An internet-based survey was distributed and completed by 178 respondents. The answers concentrated in four (among eight possible) destinations: Balneário Camboriú (31.4%), Rio de Janeiro (28%), Torres (20%) and Natal (8%). The data were first submitted to Confirmatory Factor Analysis to identify and to validate the set of components representing the Tourism Destination Image – TDI. The TDI constituting factors, and variables representing the Personal Values (as ancestors) and the Consumer Behavior (as descendants), were submitted to a Structural Equation Model to evaluate the TDI internal arrangement and inter-construct relationships. Results indicate that values related to self-respect, security and excitement influence the assessment of some TDI components, and that the last four constructs influence the likelihood of individuals to visit or to recommend the destinations.